If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(-5-4n)=87
We move all terms to the left:
3(-5-4n)-(87)=0
We add all the numbers together, and all the variables
3(-4n-5)-87=0
We multiply parentheses
-12n-15-87=0
We add all the numbers together, and all the variables
-12n-102=0
We move all terms containing n to the left, all other terms to the right
-12n=102
n=102/-12
n=-8+1/2
| 95=-5(-6a-1) | | 8x+1=6x+4 | | 11r+12=34 | | x-0.1x=5.5 | | 31-7n=-8(4-7n) | | 5x/4=9/5 | | 60-3x=40+2x | | 2x+15=2x–15 | | 2x+61=40+2x | | 32-3r=-8(1+r) | | c+8c-4=5 | | -3(x-1)+3=2 | | 2x+61=60-3x | | 32-3r=-8(1=r) | | (2+x)2.0=1.0 | | 5*5^x-5=21 | | -6x+12=-4(2x+1) | | -3(-3-b)=3b+15 | | -4c-16=20 | | 7+5(x-3)=13 | | -6(1-2n)=2n+24 | | 20r+1=1 | | -7p-22=-8(p+3) | | 42/47=x | | m+1/2=-11 | | 40x/2+6x-6/2x=0 | | p=5/3=2 | | 52+26c=-390 | | 4x-22=8-2x | | 4x+13/24=5/6-1/2x-1/3 | | 29=m4 | | 15+2(3y-1)=2y-23 |